(3Sff GdOGQbWfis - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3bGd CJi QShd Gddg Udi Gddg Ydjg hSde YGe NjHQ HbdGOI ajgG MQR eYdbI HPgH aGHJGYgG QLd HSHYI OfGfjQkG Ch HJSYI OfGfjQ s
(3BNQgG (B:s
(3abGd dg QShd Gddg Udi Gddg Ydjg hSde CfJ hCfJ bGd CfG CbOe efc hCfJ CcHQ hNjQ efi Je BNQ cJGH GdML s
(3GdLRA GdChd hGdKGfi hGdKGdK hGdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1007s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs